2014
DOI: 10.1080/00325481.2015.993572
|View full text |Cite
|
Sign up to set email alerts
|

Chronic noncancer pain management in primary care: family medicine physicians’ risk assessment of opioid misuse

Abstract: Knowledge and competency of the family physicians in managing CNCP were improved as was expected. Although the rate of eagerness about risk assessment of opioid misuse was increased, expected increase in the rate of using risk assessment was not achieved. Further studies are needed to identify the reasons of the difficulties on changing the attitudes and practices of primary care physicians about this subject.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…But, this may reflect a basic lack of understanding that many pain conditions, such as centralized pain, cannot be assessed with routine physical exam or standard X-Ray, MRI, or CT imaging techniques [ 36 ]. Consistent with the literature ([ 37 , 38 ], we also found that physicians often rely on tacit assessments of patients’ risk of aberrant drug-related behaviors, such as opioid abuse, despite recognizing they may make inaccurate assessments. Therefore, clinical leaders, educators and policymakers must continue to create and disseminate usable, evidence-based education on chronic pain and opioid risk assessment.…”
Section: Discussionsupporting
confidence: 87%
“…But, this may reflect a basic lack of understanding that many pain conditions, such as centralized pain, cannot be assessed with routine physical exam or standard X-Ray, MRI, or CT imaging techniques [ 36 ]. Consistent with the literature ([ 37 , 38 ], we also found that physicians often rely on tacit assessments of patients’ risk of aberrant drug-related behaviors, such as opioid abuse, despite recognizing they may make inaccurate assessments. Therefore, clinical leaders, educators and policymakers must continue to create and disseminate usable, evidence-based education on chronic pain and opioid risk assessment.…”
Section: Discussionsupporting
confidence: 87%
“…As such, a lot of surveys including various specialties like family physicians, surgical interns, obstetrician-gynecologists call for better opioid prescribing training and education [19-21]. In another study where the intervention group received education on the assessment of the risk of opioid misuse, the rate of eagerness to apply risk assessment increased markedly [22]. By adapting curricula to address the rising opioid epidemic, medical schools have the potential to ensure that future physicians can effectively recognize the signs, symptoms, and risks of opioid abuse and improve patient outcomes [23].…”
Section: Discussionmentioning
confidence: 99%
“…Previous provider surveys 6,[19][20][21] have identified CME as a viable means to increase provider knowledge and competency in managing CNCP. A pre-post survey of 45 resident physicians who underwent a focused educational training module on opioid prescribing for CNCP demonstrated increased knowledge and confidence in opioid prescribing.…”
Section: Discussionmentioning
confidence: 99%